Systematic review and meta‐analysis of oral paracetamol versus combination oral analgesics for acute musculoskeletal injuries. (31st August 2020) - Scott, Gemma; Gong, Jiayi; Kirkpatrick, Carl; Jones, Peter
Abstract : The aim of this systematic review and meta‐analysis was to determine if a combination of analgesics conveys any significant clinical benefit over paracetamol alone in managing acute musculoskeletal injuries. Six studies were identified ( n = 1254) and overall there was no clinically important difference between groups for reduction in pain score in the first 2 h, 24 h or 72 h. In conclusion, paracetamol monotherapy is a reasonable first‐line analgesic for acute musculoskeletal injuries as combining additional oral agents does not result in any significant additional analgesic effect. Abstract: Objective: The aim of this systematic review and meta‐analysis was to determine if a combination of analgesics conveys any significant clinical benefit over paracetamol alone in managing acute musculoskeletal injuries. Methods: Two reviewers independently searched MEDLINE (via PubMed), EMBASE and Cochrane electronic databases. Randomised controlled trials comparing paracetamol with paracetamol plus other oral analgesics in managing acute musculoskeletal injuries (e.g. sprains, contusions) were identified. Outcomes were reduction in pain score, adverse events and need for additional analgesia. Studies were critiqued using the Cochrane Risk of Bias Assessment Tool and data analysed using RevMAN meta‐analysis software. Results: Six studies were included ( n = 1254). No paediatric studies were identified. Five studies compared paracetamol to paracetamol plus NSAID. One study also included an opioid in the combination group. There was no clinically important difference between groups for reduction in pain score in the first 2 h, 24 h or 72 h. At 2 h the mean difference in reduction in pain score at rest on 100 mm VAS was 0.72 mm (−1.36, 2.79), P = 0.5. On activity it was −1.79 mm (−4.08, 0.49), P = 0.12. The risk of adverse events in ED was −0.00 (−0.04, 0.03). More patients receiving combination therapy required additional analgesia in the first 2 h: −0.03 (−0.06, −0.01), P = 0.01. Conclusion: Paracetamol monotherapy is a reasonable first‐line analgesic for acute musculoskeletal injuries as combining additional oral agents does not result in any significant additional analgesic effect.